Treatment Response to Botulinum Neurotoxin-A in Children With Cerebral Palsy Categorized by the Type of Stretch Reflex Muscle Activation - Bar-On, Lynn; Aertbeliën, Erwin; Van Campenhout, Anja; Molenaers, Guy; Desloovere, Kaat (Frontiers in Neurology, 2020)
While botulinum Toxin-A (BoNT-A) injections are frequently used to reduce the effects of hyperactive stretch reflexes in children with cerebral palsy (CP), the effects of this treatment vary strongly. Previous research, combining electromyography (EMG) with motion analysis, defined different patterns of stretch reflex muscle activation in muscles, those that reacted more to a change in velocity (velocity dependent –VD), and those that reacted more to a change in length (length dependent –LD). The aim of this study was to investigate the relation between the types of stretch reflex muscle activation in the semitendinosus with post-BoNT-A outcome as assessed passively and with 3D gait analysis in children with spastic CP. Eighteen children with spastic CP (10 bilaterally involved) between the ages of 12 and 18 years were assessed before and on average, 8 weeks post-treatment. EMG and motion analysis were used to assess the degree and type of muscle activation dependency in the semitendinosus during passive knee extensions performed at different joint angular velocities. Three-dimensional gait analysis was used to assess knee gait kinematics as a measure of functional outcome. Pre-treatment, 9 muscles were classified as VD and 9 as LD, but no differences between the groups were evident in the baseline knee gait kinematics. Post-treatment, stretch reflex muscle activation decreased significantly in both groups but the reduction was more pronounced in those muscles classified pre-treatment as VD (-72% vs -50%, p=0.005). In the VD group, these changes were accompanied by greater knee extension at initial contact and during the swing phase of gait. In the LD group, there was significantly increased post-treatment knee hyperextension in late stance. Although results vary between patients, the reduction of stretch reflex muscle activation in the semitendinosus generally translated to an improved functional outcome, as assessed with 3D gait analysis. However, results were less positive for those muscles with pre-treatment length-dependent type of stretch reflex muscle activation. The study demonstrates the relevance of categorising the type of stretch reflex muscle activation as a possible predictor of treatment response.